2008
DOI: 10.1080/13561820701795374
|View full text |Cite
|
Sign up to set email alerts
|

Exploring adolescent complementary/alternative medicine (CAM) use in Canada

Abstract: A qualitative study using a grounded theory approach investigated adolescents' perceptions about complementary/alternative medicine (CAM) use. Adolescents, attending a clinic at the Canadian College of Naturopathic Medicine, were interviewed after receiving ethics approval. Data were collected using semi-structured interviews. The decision of adolescents to use CAM was based within the context of their world and how it shaped influencing factors. Factors that influenced adolescents' decision to use CAM were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The beliefs expressed above may be attributable to the users’ perceived efficacy of the CAM. These beliefs and speculations are consistent with previous reports on reasons for CAM use in other populations [67–69]. …”
Section: Discussionsupporting
confidence: 92%
“…The beliefs expressed above may be attributable to the users’ perceived efficacy of the CAM. These beliefs and speculations are consistent with previous reports on reasons for CAM use in other populations [67–69]. …”
Section: Discussionsupporting
confidence: 92%
“…In this study, the used of UM by young adults influence by peoples, internet more than by book and advertising. This study similar to previous studies that young adults can be affected by people [10,19] . The most common reason of using UM is treating illness which similar to other studies [10,12,13,19] .…”
Section: Discussionsupporting
confidence: 80%
“…This study similar to previous studies that young adults can be affected by people [10,19] . The most common reason of using UM is treating illness which similar to other studies [10,12,13,19] . In this study showed similar previous studies [20] the young adult showed positive attitude about UM.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Patients perceived the establishment of a treatment protocol involving CAM as a highly individualised process [16,26,34-36]. However, patients also felt a responsibility to investigate for themselves potential side effects of recommended medications and treatments and through CAM they sought out treatment options that…”
Section: Resultsmentioning
confidence: 99%